Association of Anterior Knee Pain (AKP) in Different Age Groups after Total Knee Replacement (TKR) - Ghareeb Ullah, Jamshed Khan, Usmanullah, Mohammad Ishaq, Muhammad Hanif, Sajawal Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this research is to assess and to determine the frequency of Anterior Knee Pain after Total Knee Arthroplasty. Study Design: Cross sectional study. Place and Duration:This Cross sectional study was conducted at Department of Orthopedic s, Khyber Teaching Hospital, KTH Peshawar in the period of eight months from june 2020 to january 2022. Introduction: Anterior Knee Pain (AKP) is one of the most commonest causes of persistent problems after knee replacement. Total Knee Arthroplasty (TKA) is a surgical procedure in which artificial joint or prosthesis replace the damage knee. A significant proportion of the patients experience AKP after TKA surgery. Methods: After recording complete history, physical examination and routine baseline investigations were performed . Post-operatively, patients were kept under observations for 5 days in ward and were discharged if indicated. Patients were followed at regular intervals and finally at the end of third month to measure the intensity of pain on VAS. Results:Out of 205 patients, 69.3% were males and 30.7% were females. Means ± SD calculated for age was 48.62±7.98 years, for BMI was 24.63±3.07 and for Pain on VAS was 1.31±1.39. Most patients (51.7%) were recorded in 51-60 years age group. Rheumatoid Arthritis (RA) in 18% while Osteoarthritis (OA) (OA) was found in 82% patients. 21.5% patients were diabetic while 31.7% patients were hypertensive. AKP at third month was found in 8.8% patients. Conclusion: It is evident that anterior knee pain (AKP) after the total knee arthroplasty (TKA), or total knee replacement (TKR) is prevalent and clinically relevant. There is an absolute need for further investigations to find out ways to reduce or eliminate the AKP after TKA in order to improve the quality of life after this surgery. Keywords: Anterior knee pain, Arthroplasty, Total knee replacement.